Pursuing meaning - Borg, Emma. (Oxford : Oxford University Press, 2012)
Emma Borg examines the relation between semantics and pragmatics, and assesses recent answers to fundamental questions of how and where to draw the divide between the two.
Description based on online resource; title from home page (viewed on July 12, 2012).
Keywords: Semantics (Philosophy)